Convalescent Plasma: A Potential Treatment for COVID-19 - Khan, Mohiuddin Ahmed; Akter, Mafruha (Journal of Bangladesh College of Physicians and Surgeons, 2020)
As no specific standard therapies have been approved for Coronavirus disease 2019 (COVID-19), so prevention and supportive care dominate the approach to COVID-19. Exposure to this severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) results in an adaptive immune response that commonly include antibodies with neutralization activity. Treatments directly targeting the virus and the inflammatory response to it remain investigational. Convalescent plasma (CP) is such a therapy that had been reported hundred years back in studies from the Spanish influenza era. So the idea of convalescent plasma from subjects who have recovered from viral infections has been used to both prevent or treat disease. Over the past two decades’ notable examples of the successful use of convalescent plasma (CP) include influenza, measles, Middle East respiratory syndrome (MERS), Ebola and severe acute respiratory syndrome (SARS). Two case series were recently published by China examining the therapeutic use of CP in patients with COVID-19. In the context of pandemic situation, the Food and Drug Administration (FDA) allowed to use COVID-19 convalescent plasma as Investigational New Drug (IND) since April 2020 to help patients with serious or immediately life-threatening illness associated with COVID- 19. Case series studying convalescent plasma use in the treatment of COVID-19 have been promising, but additional, high-quality studies are needed to determine the efficacy of the treatment when applied for prophylaxis, for early phases of illness and for severe illness. Bangladesh also started program to use convalescent plasma for severe and critical COVID-19 patients under limited clinical trial. J Bangladesh Coll Phys Surg 2020; 38(0): 109-115